Development of Hydropower Turbines Powered by Dam Overflow - Oyebode, O. O.; Olaoye, J. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The epileptic power supply in most rural areas in Nigeria and its attendant negative impact on the economy of the Nation, Agricultural productivity and huge rural emigration, is a serious source of concern. This necessitated the development of two hydro-power turbines powered by the overflow (which was rather considered a waste) from University of Ilorin (UNILORIN) dam. A portion of the overflow was channeled into a Polyvinyl Chloride (PVC) pipe and the flow rate was calculated to be 0.017m3/sec using the bucket method. The change in elevation between the overflow and the point of usage was reported to be 4m. The flow (Q) and Head (h) were typical values for many streams and rivers in different rural areas of Nigeria, hence its suitability and adoption for this study. Two turbines viz: Pelton Wheel (PW) and Cross Flow (CF) were developed and tested. The PW generated a speed of 538.4rpm and a torque of 46.2kNm at off load condition while the CF generated a speed of 330.1rpm and a torque of 39.07kNm at the same condition. During loading – when the alternator had been connected to the turbine - the PW turbine speed and torque became 392.0rpm and 36.5kNm respectively, while that of the CF became 197.7rpm and 25.0kNm respectively. A belt and pulley mechanism was used to deliver the rotational speed to the alternator and this increased the alternator speed from the PW and CF turbines to 1768.6rpm and 879.24rpm respectively. The speed from the PW was enough to power the alternator as the alternator only requires 1500rpm to function optimally. The PW was thus adjudged the most suitable for use.